Similar meanings in different buildings, a study of examples of Arabic proverbs - Saja jassim ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
This study dealt with the theme of Arabic proverbs because of its great importance. The study focused on a main objective represented in showing the reasons for the agreement of meanings and the difference of constructs, which are due to the multiplicity of human experiences and the difference of environments, social classes, and the differences in cultures and ideas among the individuals of society. Thus, all these factors that were mentioned lead to a difference in expression and a difference in the use of appropriate utterances in specific situations. The results of the study clearly confirmed the existence of this difference by analysing samples of Arab proverbs that this study involved. The significance of this study lies in clarifying the importance of the proverbs and their effective role in daily life throughout the ages, because the proverbs have a great impact for the receiver and the user at the same time.